Determination of stigmasterol hydroperoxides using high-performance liquid chromatography-mass spectrometry with atmospheric pressure chemical ionization - S. Kemmo; V. Ollilainen; A.-M. Lampi; V. Piironen (Czech Journal of Food Sciences, 2004)
A new specific method using high-performance liquid chromatography-mass spectrometry (HPLC-MS) for the detection of stigmasterol hydroperoxides was developed. Hydroperoxides of stigmasterol were obtained by photo-oxidation (90 min) in the presence of methylene blue as a sensitizer. The separation was performed using normal-phase chromatographic conditions. The MS detection was carried out with an ion-trap mass spectrometer using atmospheric pressure chemical ionization (APCI) and positive ion mode. Stigmasterol hydroperoxides were seen to produce no protonated molecular ions [M + H]+ but instead fragments representing loss of one or two water molecules [M - H2O + H]+, [M - 2H2O + H]+, loss of hydrogen peroxide [M - H2O2 + H]+ or loss of hydrogen peroxide and water [M - H2O2 - H2O + H]+. The results showed that positional isomers of hydroperoxides had different fragmentation patterns and relative ion abundances. On the other hand anomeric isomers had more similar fragmentation. As a conclusion the method developed showed to be a useful tool for investigation the oxidation mechanism of sterols.